ZIKA VIRUS INFECTION: IMPORTANT CONCERN - Wiwanitkit, Viroj (Journal of Ayub Medical College Abbottabad, 2016)
Dear Editor, The articles on Zika virus infections in the journal are very interesting.1,2 Shoaib et al. noted for the importance of preventive public health measures at the community level and avoids travelling to the endemic areas.1 Abbasi noted that prevention can be a multi-pronged strategy and these entail vector control interventions, personal protection, environmental sanitation and health education among others.2 Indeed, Zika virus infection becomes the important public health issue at present due to its worldwide spread. Focusing on the suggestion on avoidance travelling to the endemic areas, it can be useful. But the real present problematic situation is the imported infection from both returning travellers and foreigners who carry diseases from endemic areas. The public health measure has to start at the immigration port. In case of China, the strict control can early help detect the infected case at Taipei and this can result in success in disease control and cessation of further local transmission in Taiwan.3 For the local people in endemic area, the prevention of disease might be very difficult. The Zika virus infection can be asymptomatic and transmission by mosquito to others easily occurs.4 Though many mosquito control process are set, they are usually ineffective. The important concern is the infection is usually mild and the main problem is usually on the reproductive age female. Another effective preventive measure that should not be forgotten is the use of contraception.5